Research Ethics of Becoming: Approaches Beyond Moral Laws. Issue 4 (November 2019) - Johansson, Lotta; Hall, Jeffrey B.
This article explores the postqualitative notion of "ethics of becoming" through a critique of common understandings of ethical approaches to research. By applying Deleuze's reading of Spinoza, the ethics of becoming are discussed using empirical examples from field studies. Attention is given to how ethically challenging moments arise in the imminent space beyond humanism, in which commonly acknowledged handbooks insufficiently prepare the researcher for what is to (be)come. The analysis demonstrates that an ethic of becoming does not direct attention toward moments of stability, as universal ethics usually do, but toward the situation of becomings and of new relations that are created in the moments of research.